Materials for the study of late antique and medieval Greek and Latin inscriptions in Istanbul. A revised and expanded booklet - Toth, I; Rhoby, A (Verlag der Österreichischen Akademie der Wissenschaften, 2020)
The volume 'Materials for the Study of Late Antique and Medieval Greek and Latin Inscriptions in Istanbul' is a revised and updated edition of the booklet originally produced for the Summer Programme in Byzantine Epigraphy. This collection of 37 essays has been prepared by Ida Toth and Andreas Rhoby to provide a broad coverage of Istanbul's inscriptional material dating back to the period between the 4th and the 15th centuries. It is intended as a comprehensive teaching tool and also as a dependable vademecum to the extant traces of Istanbul’s rich late antique and medieval epigraphic legacy.